Harnessing the Potential of Nutraceutical Products for Export Diversification and Development in Landlocked Developing Countries - United Nations Conference on Trade; Development (United Nations, 2023)
The present publication examines the potential, opportunities and challenges facing selected LLDCs from Africa, Asia, and Latin America (in particular, Azerbaijan, Bhutan, Bolivia, Burkina Faso, Ethiopia, and Nepal) in making the best of their biodiversity and biogenetic resources where they have comparative advantages and prospects for export diversification, value addition and structural transformation. In this context, the study explores the potential and constraints to fully harnessing health foods and nutraceuticals to enhance export diversification and improve socioeconomic conditions. It also analyses product and sector-specific challenges and opportunities and proposes a series of country-specific policy recommendations to harness the potential of nutraceutical products for socioeconomic transformation in the selected countries.